GINER PRODUCTION TECHNOLOGY - Prem Singh Arya; Prem Singh Arya (Ludhiana Kalyani, 2001)
This book is the outcome of compilation based on the research work done by the author, his practical expeience , various reports , important reviews, journals and research papers.
Ginger storage Ginger Preparation Mango Ginger
Keywords: Ginger storage ,Ginger Preparation ,Mango Ginger